A study of impacts on online purchase behaviour: information richness and website interactivity perspectives. (1st January 2012) - Ye, Lili; Chen, Zhihao; Li, Xueni
The study investigates the factors of customers' online purchase behaviour from the perspectives of information richness and website interactivity. Adopting the experimental method and content analysis, the study divides information richness into two dimensions of informational breadth and depth, namely the diversity and quality on information display. The study also divides website interactivity into two dimensions of intelligent search and interactive inquiry, which are respectively further analysed from two corresponding aspects of interactive behaviour and mutual communication. Finally, this study reaches a conclusion that the response time is gradually becoming shorter with the richer information and that the impact of information richness and website interactivity on the online purchase behaviour would vary with the different categories of products.